2021
DOI: 10.1115/1.4052137
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Unsteady Combustor Turbine Interaction for Flexible Power Generation

Abstract: In the present study low-frequency disturbances introduced by a periodic load variation have been simulated and superimposed to the inhomogeneous, unsteady flow entering a 3-stage, high-pressure industrial gas turbine fed by a can-type combustion chamber comprising 6 silo-burners. The effects of the unsteadiness realized at the combustor exit have been investigated by means of Detached Eddy Simulations, whereby a density-based solution approach with detailed thermodynamics has been employed. The periodic distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The vane potential effect did not change the temperature patterns noticeably but significantly affected the radial and azimuthal mass flow distribution. Lo Presti et al [10] simulated a full-annulus of a three-stage turbine with multi-species to resemble the combustion mixture composition. The results showed that the unsteady inlet boundary conditions increased the mixing, leading to a more uniform temperature profile.…”
Section: Introductionmentioning
confidence: 99%
“…The vane potential effect did not change the temperature patterns noticeably but significantly affected the radial and azimuthal mass flow distribution. Lo Presti et al [10] simulated a full-annulus of a three-stage turbine with multi-species to resemble the combustion mixture composition. The results showed that the unsteady inlet boundary conditions increased the mixing, leading to a more uniform temperature profile.…”
Section: Introductionmentioning
confidence: 99%